Tool Development for Cancer Patients' Sexuality Information Needs - Yeon Hee Kim; Hae Won Kim; Mikyung Kwon (Korean Society of Women Health Nursing, 2015)
PURPOSE: This study aimed to develop a scale measuring sexuality information needs of patients with cancer. METHODS: Nine items of sexuality information needs were based on the PLISSIT model and concepts of sexual rights. A factor analysis using principal axis factoring and Cronbach's alpha were performed to test validity and reliability. Data were collected from 211 patients with cancer visiting a cancer center in Seoul, Korea. RESULTS: Factor loadings of the 9 items of sub scales ranged from .43 to .96. Three factors in this study explained 74.4% of the total variance. Cronbach's alpha of the 9 items was .83. CONCLUSION: The scale of information needs about sexuality showed acceptable construct validity and reliability. This scale would be useful to assess the levels of information needs for sexuality for patients with cancer. The possibility of the scales' expansion to other group could be investigated in future studies.